DIGITAL COMMUNICATION GOVERNANCE IN THE MANAGEMENT OF ZAKAT AT THE NATIONAL ZAKAT AGENCY (BAZNAS) - Ahmad Munawaru Zaman; Dodo Murtado (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2026)
Digital communication governance plays a strategic role in boosting zakat fund collection. This study aims to analyze digital communication strategies and their effectiveness in increasing zakat collection. Employing a descriptive qualitative approach, the study gathered data through document analysis, observation of zakat institutions' communication activities, and a literature review on governance and public communication. The results indicate that zakat institutions implementing principles of information transparency, two-way dialogue, and digital media utilization tend to achieve higher levels of zakat collection. However, challenges persist regarding the consistency of information dissemination, limited digital literacy among some mustahik (beneficiaries), and suboptimal public feedback mechanisms. These findings underscore the importance of integrating good governance with participatory digital communication strategies to enhance the effectiveness of zakat management and boost zakat collection by BAZNAS. Keywords: Governance, Digital Communication, zakat